2014
DOI: 10.1186/1756-9966-33-55
|View full text |Cite|
|
Sign up to set email alerts
|

A novel miR-219-SMC4-JAK2/Stat3 regulatory pathway in human hepatocellular carcinoma

Abstract: BackgroundTo understand the involvement of structural maintenance of chromosome 4 (SMC4) in the development and progression of hepatocellular carcinoma (HCC).MethodsReal-time quantitative PCR and Western Blotting were applied to measure the expression of SMC4 in HCC samples and cell lines. The tumor-promoting effect of SMC4 was determined by WST-1, soft agar colony formation, cell motility and invasion assays. The SMC4 target signal pathway was identified by luciferase reporter and real-time quantitative PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 42 publications
4
72
0
Order By: Relevance
“…One of the hallmarks of inactivation of the JAK-STAT signaling pathway is the restriction in translocation of the nuclear and accumulated STAT3 in the cytoplasm [42]. Moreover, recent studies have revealed the importance of the JAK/STAT pathway in the development of HCC and have indicated that JAK/STAT inhibitors might be able to be used in the treatment of HCC [21,43].…”
Section: Discussionmentioning
confidence: 99%
“…One of the hallmarks of inactivation of the JAK-STAT signaling pathway is the restriction in translocation of the nuclear and accumulated STAT3 in the cytoplasm [42]. Moreover, recent studies have revealed the importance of the JAK/STAT pathway in the development of HCC and have indicated that JAK/STAT inhibitors might be able to be used in the treatment of HCC [21,43].…”
Section: Discussionmentioning
confidence: 99%
“…The cells that had invaded into the bottom surface of the filter were fixed with methanol and stained with hematoxylin. The invasive ability was determined by counting the penetrating cells under a microscope at ×400 magnification on 5 random fields in each well [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Brachyury is located at 6q27, which is a frequently amplified region in HCC [12]. The function of Brachyury has extensively been characterized in mice and zebrafish [13,14].…”
Section: Introductionmentioning
confidence: 99%